Use of Plasma for Acquired Coagulation Factor Deficiencies in Critical Care - Shah, Akshay; McKechnie, Stuart; Stanworth, Simon (Seminars in Thrombosis and Hemostasis, 2016)
Coagulopathy in critically ill patients is common and often multifactorial. Fresh frozen plasma (FFP) is commonly used to correct this either prophylactically or therapeutically. FFP usage is mainly guided by laboratory tests of coagulation, which have been shown to have poor predictive values for bleeding. Viscoelastic tests are an attractive option to guide hemostatic therapy, but require rigorous evaluation. The past few years have seen a gradual reduction in national use of FFP potentially due to an increased awareness of risks such as transfusion-related acute lung injury, patient blood management strategies to reduce transfusion in general, and increased awareness of the lack of high-quality evidence available to support FFP use. Within critical care, FFP is administered before invasive procedures/surgery, to treat major traumatic and nontraumatic hemorrhage, disseminated intravascular coagulation, and for urgent warfarin reversal if first-line agents, such as prothrombin complex concentrate (PCC) are not available. Alternative agents such as fibrinogen concentrate and PCC need further evaluation through large-scale clinical trials.
Keywords: coagulopathy; critical care; fresh frozen plasma